2001
DOI: 10.1046/j.1365-3024.2001.00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Murine schistosomiasis mansoni: coordinate cytokine regulation and differences in cellular immune responses of granuloma cells and splenocytes to endogenous and exogenous schistosome egg antigens

Abstract: To better understand the cellular immune mechanisms that regulate granulomatous inflammation to Schistosoma mansoni ova, we examined the dynamics of lymphocyte proliferation and cytokine expression by granuloma cells and splenocytes to endogenous and exogenous schistosome egg antigen (SEA) 6-19 weeks postinfection. Compared to splenocytes, granuloma cells (partially CD4+ cells) which are at the site of antigen release were highly activated by endogenous SEA and terminally differentiated as indicated by the mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 36 publications
3
18
0
Order By: Relevance
“…6C). This was consistent with previous observations of the development of SEA-reactive lymphocytes in the spleen before their detection in granuloma-infiltrating cells (39). Phillips and coworkers (40) have also shown that activated cells home to granulomas, although they did not address the role of Ag specificity.…”
Section: Figure 8 Absence Of S Mansoni-induced Liver Granuloma Formsupporting
confidence: 92%
See 2 more Smart Citations
“…6C). This was consistent with previous observations of the development of SEA-reactive lymphocytes in the spleen before their detection in granuloma-infiltrating cells (39). Phillips and coworkers (40) have also shown that activated cells home to granulomas, although they did not address the role of Ag specificity.…”
Section: Figure 8 Absence Of S Mansoni-induced Liver Granuloma Formsupporting
confidence: 92%
“…Phillips and coworkers (40) have also shown that activated cells home to granulomas, although they did not address the role of Ag specificity. Both groups found that splenic lymphocytes have a higher proliferative capacity, suggesting that both systemic expansion and activation play a role in the recruitment of lymphocytes to granulomatous sites (39,40).…”
Section: Figure 8 Absence Of S Mansoni-induced Liver Granuloma Formmentioning
confidence: 99%
See 1 more Smart Citation
“…31 High levels of IL-4 endogenously produced by the egg granuloma cells 69 could inhibit proliferation of Th1 cells. High levels of IL-10 produced by regulatory CD4 ϩ CD25 ϩ cells and macrophages in the granulomas can inhibit both Th2 and Th1 responses 69 -72 and the abundant alternatively activated macrophages are crucial in preventing severe Th1-dependent inflammatory disease.…”
Section: Discussionmentioning
confidence: 99%
“…Somular antigens which cross-react with SEA (85) must induce this early development and expansion of SEA-reactive lymphocytes. Thus, in a mouse 4 weeks postinfection, when egg laying begins and several weeks before HG appear, SEA-reactive lymphocytes are primed and proliferate in the spleen (78). These SEA-reactive lymphoblasts are then recruited into the HG (121).…”
Section: Granuloma Formationmentioning
confidence: 99%